2005
DOI: 10.1007/bf03324578
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb function as predictor of falls and loss of mobility with social repercussions one year after discharge among elderly inpatients

Abstract: Lower limb mobility tests performed in an acute care hospital setting are predictive of future falls, inability to leave home, and/or need for nursing home care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 57 publications
0
33
0
1
Order By: Relevance
“…Select correlates of SPPB could explain it. For instance, SPPB has been accreditated for predicting falls, 32 and falls, in turn, mark a dramatic decline of personal independence through a variety of mechanisms. 33 Furthermore, SPPB can reveal slowing of the walk, which is the hallmark of highly disabling conditions, such as Parkinson disease, deconditioning, arthritis, and other medical co-morbidities (e.g., hypothyroidism), and predicts further decline in functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Select correlates of SPPB could explain it. For instance, SPPB has been accreditated for predicting falls, 32 and falls, in turn, mark a dramatic decline of personal independence through a variety of mechanisms. 33 Furthermore, SPPB can reveal slowing of the walk, which is the hallmark of highly disabling conditions, such as Parkinson disease, deconditioning, arthritis, and other medical co-morbidities (e.g., hypothyroidism), and predicts further decline in functioning.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, SPPB has been shown to be highly predictive of falls, 46 which, in turn mark a dramatic decline of personal independence through a variety of mechanisms. 47 Furthermore, SPPB can reveal slowing of walking, which is the hallmark of highly disabling conditions, such as Parkinson disease, deconditioning, arthritis, and other medical co-morbidities (e.g., hypothyroidism), and predicts further decline in functioning.…”
Section: Discussionmentioning
confidence: 99%
“…This test was performed only after the elderly person demonstrated their ability to stand without using their arms. Previous studies have shown that the SPPB can predict disability, institutionalization, falls, and mortality among older adults [13141516]. A score ranging from 0 to 4 (0, inability to complete the task; 4, highest level of function) was given for each task in the SPPB, with the sum of these three tests (0–12) reflecting the complete measurement of physical function [13].…”
Section: Methodsmentioning
confidence: 99%